Fatty Acid‐Derived Pro‐Toxicants of the Rat Selective Toxicant Norbormide. Issue 6 (2nd June 2016) - Choi, Hans; Conole, Daniel; Atkinson, Darcy J.; Laita, Olivia; Jay‐Smith, Morgan; Pagano, Mario Angelo; Ribaudo, Giovanni; Cavalli, Maurizio; Bova, Sergio; Hopkins, Brian; Brimble, Margaret A.; Rennison, David
Abstract : Norbormide [5‐( α ‐hydroxy‐ α ‐2‐pyridylbenzyl)‐7‐( α ‐2‐pyridylbenzylidene)‐5‐norbornene‐2, 3‐dicarboximide] (NRB), an existing but infrequently used rodenticide, is known to be uniquely toxic to rats but relatively harmless to other rodents and mammals. However, as an acute vasoactive, NRB has a rapid onset of action which makes it relatively unpalatable to rats, often leading to sublethal uptake and accompanying bait shyness. A series of NRB‐derived pro‐toxicants (3a  – i, 4a  – i, and5a  – i ) were prepared in an effort to 'mask' this acute response and improve both palatability and efficacy. Their synthesis, in vitro biological evaluation (vasocontractile response in rat vasculature, stability in selected rat media) and palatability/efficacy in Sprague–Dawley, wild Norway, and wild ship rats is described. Most notably, pro‐toxicant3d was revealed to be free of all pre‐cleavage vasoconstrictory activity in rat caudal artery and was subsequently demonstrated to release NRB in the presence of rat blood, liver, and pancreatic enzymes. Moreover, it consistently displayed a high level of acceptance by rats in a two‐choice bait‐palatability and efficacy trial, with accompanying high mortality. On this evidence, fatty acid ester prodrugs would appear to offer a promising platform for the further development of NRB‐derived toxicants with enhanced palatability and efficacy profiles. Abstract :